THE POWER OF LEADERSHIP: UNVEILING THE ROLE OF LEADERSHIP ON TEACHERS' MOTIVATION AT THE SECONDARY LEVEL (Contemporary Journal of Social Science Review, 2025)
The success of any educational system significantly depends on the motivation and performance of its teachers, which are, in turn, greatly influenced by the leadership practices of school administrators. This study aimed to investigate the relationship between principals’ leadership styles and teachers’ motivation in public sector male secondary schools of District Lahore. Grounded in Bass and Avolio’s Full Range Leadership Theory and Herzberg’s Two-Factor Theory of Motivation, the study explored how transformational, transactional, and laissez-faire leadership styles impact intrinsic and extrinsic motivation among secondary school teachers.A quantitative research design was employed to ensure objective measurement and analysis. The target population included approximately 3,300 male teachers from 73 public sector male secondary schools in Lahore. Using a two-stage random sampling technique, data were collected from 200 teachers across 20 randomly selected schools. A structured questionnaire was adopted, validated through expert reviews, and pilot-tested to confirm its reliability. Data were analyzed using descriptive statistics, Pearson correlation, and regression analysis. The findings revealed a positive relationship between transformational leadership and both intrinsic and extrinsic teachers’ motivation. Transactional leadership also showed a moderate positive impact, while laissez-faire leadership had a weak and often negative correlation with teacher motivation. The results emphasized that leadership style is a crucial determinant of teacher engagement, satisfaction, and professional commitment. This study provided valuable insights for policymakers, educational leaders, and training institutions in Pakistan